KEPUASAN KERJA MEMODERASI PENGARUH GAYA KEPEMIMPINAN TRANSAKSIONAL DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG (KPKNL) AMBON - Christian Bernardo; Gerrit M Pentury; Ferdy Leuhery (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2023)
This study aimed to determine the effect of transactional leadership style and work motivation to organizational performance with job satisfaction as a moderating at the State Assets and Auction Service Office (KPKNL) Ambon. The data collection method used was a questionnaire with non-probability sampling techniques which included saturated sampling and obtained 32 respondents. The data analysis technique used is Moderated Regression Analysis (MRA) by conducting a determination coefficient test, model feasibility test and t test to test the hypothesis. Based on the results showed that transactional leadership style has a positive effect on employee performance, work motivation has a positive effect on organizational performance. The results also show that job satisfaction is not able to moderate the effect of transactional leadership style on employee performance, nor is job satisfaction able to moderate the effect of work motivation on employee performance